Proposta de um modelo de gestão da manutenção para uma empresa do ramo metalúrgico - RODRIGUES, Dárleth Cantão (2021)
Organizations can be represented as a system composed of several activities that, despite the different characteristics, work together to achieve the goals defined by the company. Equipment maintenance activities are important for quality assurance, so in the pursuit of staying in the existing competitive market, organizations should look for ways to manage maintenance efficiently. The metallurgical company, object of study of this work, did not have a well-structured maintenance management, there were several deficits that made it impossible to adjust to market requirements. This work aims to structure a Maintenance Management system in a systematic and documentary way in a company of the metallurgical branch, located in Abaetetuba - PA. For this purpose to be achieved, a series of steps with defined activities and a schedule with the period of study, execution and evaluation was established, which defined the maintenance management in the company. This work followed the commands proposed in the PDCA cycle to reach the objectives, the first step was the data collection of machines and maintenance to map the existing machinery, from this stage began to think of maintenance concepts in order to adapt this knowledge. the reality of the company. With the adapted management model based on TPM and TQmain, the next stage was the creation of system support documents to structure the bureaucratic part of the management model, followed by prioritization of machine maintenance within the organization. through a criticality assessment of the equipment. From the creation of the control system, it was possible to observe the maintenance behavior and prove the efficiency of the information provided. In order to adapt the employees to the proposed management model, there were face-to-face training and the creation of a manual with management guidelines. The obtained results demonstrated the dynamics of the created system, as well as its effectiveness. These results were important for the realization that the proposed management model offers the necessary support for the maintenance of the company, focusing on employees and the maximum permanence of equipment in good use.